Frances Gateward and John Jennings. The Blacker the Ink: Constructions of Black Identity in Comics and Sequential Art. Rutgers UP, 2015. - Evan B Thomas (Studies in 20th & 21st Century Literature, 2017)
Review of Frances Gateward and John Jennings. The Blacker the Ink: Constructions of Black Identity in Comics and Sequential Art. Rutgers UP, 2015.
Keywords: comics; comic books; graphic novels; race; identity